2017
DOI: 10.1039/c7sm00719a
|View full text |Cite
|
Sign up to set email alerts
|

Twisting with a twist: supramolecular helix fluctuations in chiral nematics

Abstract: Most theoretical descriptions of lyotropic cholesteric liquid crystals to date focus on homogeneous systems in which the rod concentration, as opposed to the rod orientation, is uniform. In this work, we build upon the Onsager-Straley theory for twisted nematics and study the effect of weak concentration gradients, generated by some external potential, on the cholesteric twist. We apply our theory to chiral nematics of nanohelices in which the supramolecular helix sense is known to spontaneously change sign up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This observation of right‐handed charity from a left‐handed amyloid fibril indicates that the cholesteric phase of HEWL fibrils shares the same mechanism of chirality inversion of β‐lactoglobulin fibrils. [ 6,23,37 ] However, the sequence of chirality inversion is opposite to those found in DNA, [ 38 ] cellulose, [ 5 ] and virus, [ 39 ] where right‐handed rods develop left‐handed cholesteric phases. The size‐dependent morphological transitions characterizing the tactoids are shown in Figure 2g.…”
Section: Resultsmentioning
confidence: 99%
“…This observation of right‐handed charity from a left‐handed amyloid fibril indicates that the cholesteric phase of HEWL fibrils shares the same mechanism of chirality inversion of β‐lactoglobulin fibrils. [ 6,23,37 ] However, the sequence of chirality inversion is opposite to those found in DNA, [ 38 ] cellulose, [ 5 ] and virus, [ 39 ] where right‐handed rods develop left‐handed cholesteric phases. The size‐dependent morphological transitions characterizing the tactoids are shown in Figure 2g.…”
Section: Resultsmentioning
confidence: 99%
“…Annealing has several consequences: (1) A chemical gradient is generated between the two layers in a direction perpendicular to the film surfaces, which produces a physical pitch gradient in the transverse direction. The generation of pitch-gradient cholesterics has been carefully investigated and discussed, and the modeling of the reflection wavelength with respect to the pitch in the case of a graded twist has been addressed several times; these results are beyond the scope of this study. (2) A homeotropic orientation of molecules is induced perpendicular to the bilayer surface surrounding the green film–air interface between two consecutive polymer stripes while the planar orientation below the stripes is maintained (Supporting Information: On the polygonal texture).…”
Section: Resultsmentioning
confidence: 99%
“…fd-virus and DNA origami rods) used in experiments of colloidal membranes. For example, using a "straight and helically-decorated" model [2,57] would allow us to compare the computational and experimental results more directly. Meanwhile, recent experiments have shown that the shape fluctuation of chiral rods also dramatically affects their assembled structures [58], thus it would be interesting to consider the flexibility of rod-like particles in future work.…”
Section: Discussionmentioning
confidence: 99%